Estimation of inbreeding and effective population size in Istrian cattle using molecular information - Curik, Ino; Ferenčaković, Maja; Karapandza, N.; Cubric-Curik, Vlatka; Sölkner, Johann (Acta Agraria Kaposváriensis, 2014)
To provide preliminary insight in the conservation risk status in Istrian cattle we analysed ROH inbreeding and effective population size in 15 individuals, mostly bulls, using BovineSNP50K BeadChip. We obtained very high inbreeding level, although with broad confidence interval, and very low effective population size. While the results obtained are preliminary (small sample size) and should be treated with caution, the high recent inbreeding and small effective population size suggest additional monitoring of the conservation risk status of the Istrian cattle.
Keywords: Istrian cattle; Inbreeding; Runs of homozygosity; effective population size; single nucleotide polymorphism